Multi-Ligament Knee Injuries in Elite Athletes: return to play rates, timing, and complications. Issue 7 (31st July 2020) - Jones, Mary; Ball, Simon; Williams, Andy; Borque, Kyle
Objectives: Historically, combined ligament injuries of the knee have been considered career ending for elite athletes. The objective of this paper was to provide a reference when counseling athletes and medical staffs in regards to outcomes following combined ligament knee injuries in elite athletes. Methods: A retrospective assessment of all elite athletes (professionals or amateurs at a national level) who had sustained a combined ligament knee injury in the period February 2001 to December 2015 was performed. Cases with a minimum of 2 ligaments needing surgery were included (of note, all medial collateral ligament (MCL) injuries were grade 3). The minimum follow up was 2 years. The outcomes recorded were: return to play or not, level of play returned to, time to return to play, and complications. This data was available in 100% of cases. Results: 109 procedures were performed in 108 elite athletes. The mean age was 24.3 years old. Sports represented were: soccer (60 athletes), rugby (38 athletes), Judo (3 athletes), gymnastics (3 athletes), basketball (1 athlete), cricket (1 athletes), netball (1 athlete), and skiing (1 athlete). The distribution of injuries, rate of return to play and average return time can be seen in Figure 1. 40 of the 109 (36.7%) knees operated on underwent a minimum of one more surgical procedure during this period. The most common was manipulation under anesthesia (16 out of 109), followed by arthroscopic meniscectomy (9 out of 109). 2 out of 109 knees required revision ligament reconstruction. Conclusion: This study focuses on the ability to return to play, the level of play possible, and how long recovery takes, the factors most important to elite athletes. This study is unique and provides a reference point for future work, as well as being valuable to athletes and their medical and coaching teams.With such a large experience of these challenging injuries the senior author has learned key lessons. The only injuries that must have acute surgery (within first 2-3 weeks) are: those with a vascular lesion (rare in sport); irreducible dislocation (usually 'button-holed' medial femoral condyle); PLC structure injuries; and uncontrollable grade 3 PCL. With modern bracing much of the soft tissue envelope will heal- especially MCL tears of all grades and PCL grade 1 and 2. Early surgery, especially when it involves the MCL, has a high chance of stiffness requiring surgical intervention. The majority of injuries can be braced and safely dealt with when acute inflammation has resolved and motion is restored. Some injuries are best treated with staged surgery, specifically when the PLC is involved. Even in experienced hands, these cases often require subsequent procedures. It is critical to educate the patient and the team's staff about this possibility at the onset of treatment. In addition, while the average return to play times range from 7-25 months, it takes at least 2-3 years to return to peak form due to the proprioceptive deficit sustained with these injuries. While these injuries can be career ending in elite sport, this case series shows that with modern treatment strategies and techniques, good results can be achieved in a high number of cases. Table 1. Injury Number Return to sport Return to same level Ave time taken (months) ACL + MCL 36 31 (86%) 29 (81%) 10.2 ACL + PLC 39 33 (85%) 26 (67%) 12.9 ACL + MCL + PLC 4 3 2 15 ACL + PCL 3 3 2 12.3 PCL + MCL 4 4 3 17.5 PCL + PLC 10 9 (90%) 9 (90%) 14.9 MCL + PLC 1 1 1 4 Bicruciate + MCL 4 1 1 13 Bicruciate + PLC 5 5 3 18.2 ACL/PCL/MCL/PLC 3 3 2 22 PLC = Posterolateral corner